Cytotoxic Necrotizing Factor-1 (CNF1) does not promote E. coli infection in a murine model of ascending pyelonephritis - Michaud, Jason E.; Kim, Kwang Sik; Harty, William; Kasprenski, Matthew; Wang, Ming-Hsien (BMC microbiology, 2017)
Background Urinary tract infections (UTI) are among the most common and costly infections in both hospitalized and ambulatory patients. Uropathogenic E. coli (UPEC) represent the majority of UTI isolates and are a diverse group of bacteria that utilize a variety of virulence factors to establish infection of the genitourinary tract. The virulence factor cytotoxic necrotizing factor-1 (CNF1) is frequently expressed in clinical UPEC isolates. To date, there have been conflicting reports on the role of CNF1 in the pathogenesis of E. coli urinary tract infections. Results We examined the importance of CNF1 in a murine ascending kidney infection/ pyelonephritis model by performing comparative studies between a clinical UPEC isolate strain and a CNF1-deletion mutant. We found no alterations in bacterial burden with the loss of CNF1, whereas loss of the virulence factor fimH decreased bacterial burdens. In addition, we found no evidence that CNF1 contributed to the recruitment of inflammatory infiltrates in the kidney or bladder in vivo. Conclusions While further examination of CNF-1 may reveal a role in UTI pathogenesis, our data casts doubt on the role of CNF-1 in the pathogenesis of UPEC UTI. As with other infections, different models and approaches are needed to elucidate the contribution of CNF1 to E. coli UTI.